The BMC Medicine breast cancer collection: an illustration of contemporary research and clinical care - Tripathy, Debu (BMC Med, 2015)
The field of breast cancer had witnessed clear improvements in survival and less morbidity over the last few decades owing to earlier detection as a result of public awareness and screening, as well as treatments involving the disciplines of surgical, radiation and medical oncology along with advances in imaging and pathological diagnostics. However, in the last 5–10 years, newer assays and biological therapies have begun to cross new boundaries with higher rates of cure seen in more aggressive cancers. Even though metastatic breast cancer remains incurable, some, but not all, subsets of patients with breast cancer are living longer and more productive lives. Many challenges still remain, and the development of team science coupled with collaborative clinical research and care is expected to accelerate advances along this trajectory.